Partycypacja społeczna w konstruowaniu dokumentów rozwoju zrównoważonego na przykładzie Lubelszczyzny - Legutko-Kobus, Paulina (Public participation in creation of documents on sustainable development on the example of the region of Lubelszczyzna, 2007)
The paper presents models of social participation in constructing documents of sustainable development and environmental protection programming. A socialization of the documents created in the region of Lubelszczyzna is presented on the background of theoretical models and legał basis. The considerations mostly refer to strategies of development and are related to environmental protection programmes and to the concept of eco-development in smaller degree. Presented examples of participation on regional and local level allowed to define difficulties in conducting of public consultations. These examples also allowed to draw conclusions and recommendations regarding the public participation as one of the reąuirements of sustainable development implementation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1190, s. 306-314